2015
DOI: 10.1186/1749-8090-10-s1-a330
|View full text |Cite
|
Sign up to set email alerts
|

Improving On Fast-track Protocol for Post Cardiac Surgery Patients

Abstract: Background/Introduction Many risk factors have been shown to be independently predictive of the success of fast-track for post cardiac surgery patients. While a safe fast-track protocol is important, patient selection is crucial too in determining the success of fast-tracking patients. Aims/Objectives We aim to improve on our fast-track protocol by identifying risk factors affecting extubation time in our institution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Conversely, a 2013 retrospective analysis of over 11,000 patients found age and left ventricular dysfunction were significant preoperative predictors of failure FTCA [ 20 ]. Most recently, a 2018 prospective observational study concluded that age, pre-existing renal impairment, Euroscore, inotropic requirement, aortic cross-clamp time and total cardiopulmonary bypass time were all predictors of FTCA failure [ 21 ]. To summarize, the available evidence suggests that, predictably, FTCA is more likely to be successful in younger patients with fewer comorbidities and greater baseline cardiac function, with ongoing work required to determine hard criteria for FTCA patient selection.…”
Section: Main Textmentioning
confidence: 99%
“…Conversely, a 2013 retrospective analysis of over 11,000 patients found age and left ventricular dysfunction were significant preoperative predictors of failure FTCA [ 20 ]. Most recently, a 2018 prospective observational study concluded that age, pre-existing renal impairment, Euroscore, inotropic requirement, aortic cross-clamp time and total cardiopulmonary bypass time were all predictors of FTCA failure [ 21 ]. To summarize, the available evidence suggests that, predictably, FTCA is more likely to be successful in younger patients with fewer comorbidities and greater baseline cardiac function, with ongoing work required to determine hard criteria for FTCA patient selection.…”
Section: Main Textmentioning
confidence: 99%
“…[3,16] The fi rst enhanced recovery programs in cardiovascular surgical procedures were the so-called fast-track and ultra-fast track programs, introduced in the 1990s. [17][18][19] These proposed shortening the duration of orotracheal extubation and postoperative ventilation mechanics, which are risk factors for respiratory complications, as well as shortened stays in hospitals and intensive care units (ICUs). But these actions were focused on a single stage of the perioperative period and were not multidisciplinary.…”
Section: Introductionmentioning
confidence: 99%
“…In cardiac surgery, such fasttrack and ultra fast-track programs are not applied to all cardiac surgical procedures or to all patients. [17,[19][20][21][22][23][24][25][26] Between 2017 and 2019, publications on the results of ERAS programs in cardiac surgery increased. [6,14,19,23,[27][28][29][30][31][32][33] World leaders in the specialty recognized the need to adapt the original ERAS programs to cardiac surgery patient characteristics and to each type of intervention, and to generalize a protocol based on the best scientifi c evidence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation